In Situ Investigation of Lithium Metal–Solid Electrolyte Anode Interfaces with ToF‐SIMS. Issue 13 (17th March 2022) - Otto, Svenja‐K.; Riegger, Luise M.; Fuchs, Till; Kayser, Sven; Schweitzer, Pascal; Burkhardt, Simon; Henss, Anja; Janek, Jürgen
Abstract: Solid‐state batteries with a lithium metal anode (LMA) are promising candidates for the next generation of energy storage systems with high energy and power density. However, successful implementation of the LMA requires deeper insight into the lithium metal–solid electrolyte (Li|SE) interface. Since lithium is highly reactive, reaction products form when it comes into contact with most solid electrolytes (SEs) and the resulting interphase can have detrimental effects on cell performance. To better understand the formation of interphases, Li|SE interfaces are studied with time‐of‐flight secondary‐ion mass spectrometry (ToF‐SIMS), which provides chemical information with high sensitivity in 2D as well as 3D and is a valuable complement to commonly used techniques. To investigate the interphase, lithium is deposited in situ on SE pellets either through lithium vapor deposition or electrochemical lithium plating. Subsequent depth profiling provides information about the stability of the Li|SE interface and about the microstructure of the formed interphase. At the Li|Li6 PS5 Cl interface of lithium metal with argyrodite‐type Li6 PS5 Cl, an apparently covering Li2 S‐rich layer is found as major part of the interphase. Independent of the deposition method, a combination of ToF‐SIMS and atomic force microscopy indicates a thickness of about 250 nm for the Li2 S‐rich interlayer. Abstract : Time‐of‐flight secondary‐ion mass spectrometry depth profiling is used to study the interphase formation at lithium|solid electrolyte interfaces. Lithium is deposited on solid electrolytes in situ either through vapor deposition or electrochemical plating. The stability of different interfaces, the microstructure of forming interphases, and through a combination with atomic force microscopy, roughness and thickness information are accessible.